L'école privée au service de l'attractivité territoriale ? Politiques scolaires et renouvellement urbain à Marseille - Gwenaëlle Audren (Les éditions de la Maison des sciences de l'Homme, 2020)
In a context of globalization and neoliberalization of public policies, the adoption of a "new public management" affects all areas of society, from territorial development to education. In the education sector, the role of local authorities, private institutions, and parents has been reinforced. These transformations participate in the creation of more competitive school markets where schools became urban amenities. This article demonstates how school became a pivotal aspect of urban renewal projects and promotes the development of new partnerships. Mobilizing a dual methodology drawing on both qualitative and quantitative approaches, this article more precisely underlines how school is becoming a means for urban revitalization which may increase the risks of segregation and reinforce local inequalities.